Diagnosis of nasopharyngeal carcinoma using an ultrasensitive immunoassay method based on nanoparticles. Issue 7 (27th January 2023) - Gong, Rui; Yang, Chenyang; Abbas, Ghulam; Wang, Dianbing; Zhang, Xianen; Nie, Guohui; Ding, Hui
Abstract : The rapid detection of the antibody of Epstein–Barr virus (EBV) is critical for the diagnosis of nasopharyngeal carcinoma (NPC). Abstract : The detection of the antibody of Epstein–Barr virus (EBV) is critical for the diagnosis of nasopharyngeal carcinoma (NPC). An accurate and scalable point-of-care detection method would support the screening, diagnosis, and monitoring of NPC patients. In this study, firstly, we made an antibody enrichment element, antigen-MNPs, which can screen out specific antibodies in a complex sample. Secondly, signal-amplifying elements were synthesized by labelling inorganic quantum dots (QDs) and anti-antibodies on the surface of flop-ferritin. A sandwich structure is formed among antigen-MNPs, target-antibodies, and anti-antibodies-flop-ferritin@QDs. The antibodies are quantified by fluorescence intensity with a limit of detection (LOD) as low as 10 −11 g mL −1 . Moreover, the method can detect different types of antibodies and was employed to examine 10 sera from NPC patients and 10 sera from healthy individuals. The result indicates that the simultaneous detection of anti-EBNA-IgG and anti-EBNA-IgA provides an efficient route for early diagnosis of NPC.